Winning strategies for business - Baisya, Rajat K. (Response Books, 2010)
Winning Strategies for Business is a comprehensive strategic management resource that brings together all the business tools that managers need for surviving business challenges and succeeding in the dynamic economic environment of today. The recent global economic crisis has alerted the business world to the need for maintaining a strategic edge through productivity enhancement, cost management and product innovation. The book provides a holistic and contemporary lesson on strategic management by encompassing areas like strategy development, new economic policy, strategies for survival, compe.